Between Horizontality and Centralisation: Organisational Form and Practice in the Finns Party - Hatakka, Niko (2021)
This article provides the first comprehensive analysis of the Finns Party’s (Perussuomalaiset [PS]) formal organisation and how it operates in practice. Following the framework of this thematic issue, to what extent does the PS’s organisation follow the mass-party model and how centralised is the party in its internal decision-making? Analysis of party documents, association registries, and in-depth interviews with 24 party elite representatives reveal that the PS has developed a complex organisational structure and internal democracy since 2008. However, the power of members in regard to the party’s internal decision-making remains limited, despite the party’s leadership having facilitated a more horizontal and inclusionary organisational culture after 2017. The study reveals how the party combines radically democratic elements of its leadership selection and programme development with a very high level of centralisation of formal power in the party executive, and how the party organisationally relies on a vast and autonomous but heterogeneous network of municipal associations. The article also discusses how PS elites perceive the advantages of having a wide and active organisation characterised by low entry and participation requirements, and how party-adjacent online activism both complements and complicates the functioning of the formal party organisation.